Republic of Burundi : Health Financing Study - World Bank (Washington, DC, 2012)
During the conflict, public expenditure on health drastically decreased weakening the health system at a time when needs were growing. With increasing peace and stability in the country, foreign aid and public resources allocated to the sector have started to increase. However, health authorities still face the challenge of mobilizing extra resources to reverse the damage to the health system and to progress towards achieving the Millennium Development Goals (MDGs). Nevertheless, more resources allocated to the sector will not necessarily improve health outcomes, especially for the poor, if weaknesses in public expenditure management and inefficiencies in the allocation of resources for the sector are not reduced. These challenges become more acute in the context of the presidential measure of eliminating user fees for deliveries and for child health service.